Metabolic syndrome and osteoporotic fracture: a population-based study in China. Issue 1 (December 2016) - Qin, Li; Yang, Zhen; Zhang, Weiwei; Gu, Hongxia; Li, Xiaoyong; Zhu, Lingfei; Lu, Shuai; Xing, Yin; Zhang, Hongmei; Niu, Yixin; Ning, Guang; Su, Qing
Abstract Background Associations between metabolic syndrome (MetS) and osteoporotic fracture have been reported. However, the epidemiological studies are not conclusive. The objective of the study was to determine whether metabolic syndrome associates with osteoporotic fracture. Methods This was a cross-sectional study of 9930 Chinese adults aged 40 year or older in the Chongming District, Shanghai, China. A questionnaire, anthropometric measurements and laboratory tests were conducted. MetS was defined according to the updated National Cholesterol Education Program Adult Treatment Panel III criteria for Asian-Americans. A history of fractures was collected with an interviewer-assisted questionnaire. Osteoporotic fractures were defined as fractures that occurred due to low-trauma in 2 years prior to the study. Results Among women, the prevalence of osteoporotic fractures was significantly higher in those with MetS (3.5 vs. 2.6 %, P =0.028). However, the difference was not found in men (2.6 vs. 2.4 %, P =0.737). The presence of Mets was significantly associated with increased odds of osteoporotic fracture among women (odds ratio 1.22; 95 % confidence interval 1.12–1.54;P = 0.039) after controlling for potential confounders. The significant associations were not detected in men. Conclusions The presence of MetS was significantly associated with a recent history of osteoporotic fracture in middle-aged and elderly Chinese women.